Sodium-glucose cotransporter 2 inhibitors induce anti-inflammatory and anti-ferroptotic shift in epicardial adipose tissue of subjects with severe heart failure - Kasperova, Barbora Judita; Mraz, Milos; Svoboda, Petr; Hlavacek, Daniel; Kratochvilova, Helena; Modos, Istvan; Vrzackova, Nikola; Ivak, Peter; Janovska, Petra; Kobets, Tatyana; Mahrik, Jakub; Riecan, Martin; et al. (Cardiovascular diabetology, 2024)
BACKGROUND: Sodium-glucose cotransporter 2 inhibitors (SGLT-2i) are glucose-lowering agents used for the treatment of type 2 diabetes mellitus, which also improve heart failure and decrease the risk of cardiovascular complications. Epicardial adipose tissue (EAT) dysfunction was suggested to contribute to the development of heart failure. We aimed to elucidate a possible role of changes in EAT metabolic and inflammatory profile in the beneficial cardioprotective effects of SGLT-2i in subjects with severe heart failure. METHODS: 26 subjects with severe heart failure, with reduced ejection fraction, treated with SGLT-2i versus 26 subjects without treatment, matched for age (54.0 ± 2.1 vs. 55.3 ± 2.1 years, n.s.), body mass index (27.8 ± 0.9 vs. 28.8 ± 1.0 kg/m2, n.s.) and left ventricular ejection fraction (20.7 ± 0.5 vs. 23.2 ± 1.7%, n.s.), who were scheduled for heart transplantation or mechanical support implantation, were included in the study. A complex metabolomic and gene expression analysis of EAT obtained during surgery was performed. RESULTS: SGLT-2i ameliorated inflammation, as evidenced by the improved gene expression profile of pro-inflammatory genes in adipose tissue and decreased infiltration of immune cells into EAT. Enrichment of ether lipids with oleic acid noted on metabolomic analysis suggests a reduced disposition to ferroptosis, potentially further contributing to decreased oxidative stress in EAT of SGLT-2i treated subjects. CONCLUSIONS: Our results show decreased inflammation in EAT of patients with severe heart failure treated by SGLT-2i, as compared to patients with heart failure without this therapy. Modulation of EAT inflammatory and metabolic status could represent a novel mechanism behind SGLT-2i-associated cardioprotective effects in patients with heart failure.
Keywords: tepový objem; Inflammation Mediators; Stroke Volume; metabolomika; Humans; perikard; lidé středního věku; Anti-Inflammatory Agents; Middle Aged; Sodium-Glucose Transporter 2 Inhibitors; funkce levé komory srdeční; tuková tkáň; antiflogistika; Adipose Tissue; mužské pohlaví; diabetes mellitus 2. typu; Metabolomics; Severity of Illness Index; stupeň závažnosti nemoci; výsledek terapie; srdeční selhání; biologické markery; Treatment Outcome; Epicardial Adipose Tissue; Diabetes Mellitus, Type 2; ženské pohlaví; mediátory zánětu; Pericardium; glifloziny; lidé; Heart Failure; Ventricular Function, Left; Biomarkers; Male; epikardiální adipózní tkáň; Female